Economic Globalization and Legal Sovereignty: Who Owns Copyright in Indonesia? - T. Keizerina Devi Azwar; Yati Sharfina Desiandri; Putri Rumondang Siagian (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
Economic globalization has increasingly shaped the field of intellectual property rights (IPR), transforming copyright protection from a domestic matter into a strategic tool of global trade. Through international instruments such as the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs) and the Berne Convention of 1886, universal copyright standards are enforced across jurisdictions. Yet this harmonization generates tension between international obligations and national legal sovereignty. This article employs a juridical-normative method with doctrinal, case study, and comparative approaches to examine these dynamics. The case of Auld Lang Syne illustrates how public domain works evolve into shared cultural heritage, while the dispute of Ahmad Dhani v. Once Mekel reveals persistent enforcement challenges in Indonesia. Comparative analysis of the United States, United Kingdom, Japan, and Indonesia demonstrates divergences in copyright duration, derivative work protection, and exceptions such as parody. The article argues that Indonesia must ground its response to globalization of IPR in Pancasila and the 1945 Constitution, thereby ensuring that national copyright law is not merely a passive rule taker within the global system but an active framework that safeguards cultural identity and national interests.